Ecological drivers of soil microbial diversity and soil biological networks in the Southern Hemisphere - Delgado-Baquerizo, Manuel; Reith, Frank; Dennis, Paul G.; Hamonts, Kelly; Young, Andrew; Singh, Brajesh K.; Bissett, Andrew (Ecology, 2018)
14 páginas.- 7 figuras.- 96 referencias.-Additional supporting information may be found in the online version of this article at http://onlinelibrary.wiley.com/doi/10.1002/ecy.2137/suppinf Open access in https://espace.library.uq.edu.au/view/UQ:716294 The ecological drivers of soil biodiversity in the Southern Hemisphere remain underexplored. Here, in a continental survey comprising 647 sites, across 58 degrees of latitude between tropical Australia and Antarctica, we evaluated the major ecological patterns in soil biodiversity and relative abundance of ecological clusters within a co-occurrence network of soil bacteria, archaea and eukaryotes. Six major ecological clusters (modules) of co-occurring soil taxa were identified. These clusters exhibited strong shifts in their relative abundances with increasing distance from the equator. Temperature was the major environmental driver of the relative abundance of ecological clusters when Australia and Antarctica are analyzed together. Temperature, aridity, soil properties and vegetation types were the major drivers of the relative abundance of different ecological clusters within Australia. Our data supports significant reductions in the diversity of bacteria, archaea and eukaryotes in Antarctica vs. Australia linked to strong reductions in temperature. However, we only detected small latitudinal variations in soil biodiversity within Australia. Different environmental drivers regulate the diversity of soil archaea (temperature and soil carbon), bacteria (aridity, vegetation attributes and pH) and eukaryotes (vegetation type and soil carbon) across Australia. Together, our findings provide new insights into the mechanisms driving soil biodiversity in the Southern Hemisphere. The BASE project is supported by funding fromBioplatforms Australia through the Australian Government National Collaborative Research Infrastructure Strategy (NCRIS) https://doi.org/10.1186/s13742-016-0126-5, We thank the BASE project and its contributors ...